Control of Crystallization of PBT-PC Blends by Anisotropic SiO2 and GeO2 Glass Flakes - Düsenberg, Björn; Esper, Julian Duane; Maussner, Felix; Mayerhofer, Magdalena; Schmidt, Jochen; Peukert, Wolfgang; Bück, Andreas (Polymers, 2022)
Polymer composites and blend systems are of increasing importance, due to the combination of unique and different material properties. Blending polybutylene terephthalate (PBT) with polycarbonate (PC) has been the focus of attention for some time in order to combine thermo-chemical with mechanical resistance. The right compounding of the two polymers is a particular challenge, since phase boundaries between PBT and PC lead to coalescence during melting, and thus to unwanted segregation within the composite material. Amorphization of the semi-crystalline PBT would significantly improve the blending of the two polymers, which is why specific miscibility aids are needed for this purpose. Recent research has focused on the functionalization of polymers with shape-anisotropic glass particles. The advantage of those results from their two-dimensional shape, which not only improves the mechanical properties but are also suspected to act as miscibility aids, as they could catalyze transesterification or act as crystallization modifier. This work presents a process route for the production of PBT-PC blends via co-comminution and an in-situ additivation of the polymer blend particles with anisotropic glass flakes to adjust the crystallinity and therefore enhance the miscibility of the polymers.
CRIS-Team Scopus Importer:2022-11-25
Keywords: anisotropic particles; co-comminution; crystallization modifiers; functional filler; glass flakes; polymer-blends